Phase inversion phenomena of EPDM /PP : based TPVs by Electronic Microscopy - Machado, A. V. (2009)
Morphology development during phase inversion is a very complex and not well understood process. EPDM/PP -based TPVs were prepared and characterize by different electronic microscopy techniques. Using a low Mw-EPDM, morphology development during phase inversion was successfully followed by scanning electron microscopy with a back scattered electron detector.